Decorated Pinctada Margaritifera: New Data to the Presence of Eastern People in the Civil Town of Aquincum? - Láng, Orsolya (Communicationes Archaeologicae Hungariae, 2006)
A fragment of a large decorated bi-valve shell was found in the so-called “Diana-sanctuary” (building nr. XXVI) during the excavation carried out by late E. Márity in 1993. The valve is decorated with running animals. Due to the tragic death of the excavator, the object has never been evaluated or published. Based on earlier research which identified the building complex as sanctuary and other finds from this area this shell has been commonly associated with cult activity. Here, parallels for this object will be explored as well as its function and its place within the topographic context the Civil town of Aquincum.